Transformation from paper based to Ingenious E-Attendance system (INEA) / Ramita Abdul Rahim, Sazimah Mohamed Salleh and Nur Amanina Abdul Wahab - Abdul Rahim, Ramita; Mohamed Salleh, Sazimah; Abdul Wahab, Nur Amanina (2020)
It is an important process to track the class attendance of students in every educational institution as it is directly related to academic success. The paper-based manual compilation of student attendance results in a loss of time as well as delays in the subsequent processing of the collected data. A solution for the automation, tracking, and further processing of attendance collection is proposed to help lecturer focus on teaching. The e-attendance system named "Ingenious E-Attendance" (INEA) was proposed to shorten the recording attendance duration, save cost, promote green HR implementation that reduces pollution and waste and assist to enforce punctuality and discipline on students. In addition, it offers a summary attendance report at any point in time and easily access from anywhere. By using the application, users can also notify the student's absenteeism to the guardians of the students via SMS or any appropriate instrument. The student attendance system 'INEA' can be practiced using QR code and smartphone as a medium for data recording. In addition, the use of QR code to record attendance with additional protection will be developed to avoid unauthorized registration of attendance using multifactor authentication, which is verifying username and password. The system will able to verify students' identity and prevent false registration. The location will also be checked to ensure that the students are present in the class when scanning the QR code. All of the attendance records will be recorded to the system and available to students and lecturers instantly. This proposed system is suitable to replace the current inefficient process.